Pengaruh Konsentrasi Oksida Logam CuO Sebagai Superkapasitor Berbasis Karbon Aktif - Maryati Doloksaribu; Erniwati Halawa; Mukti Hamjah Harahap (Jurnal Penelitian Pendidikan IPA, 2024)
Supercapacitors are promising energy storage devices in future energy technology. In this research, the primary and applied aspects of supercapacitors are developed. Various techniques have been developed specifically to estimate specific capacitances. Various attempts have been made in the literature to increase the specific capacitance value of the electrode materials. Electrode materials with unique structural and electrochemical properties, such as high capacity and cyclic stability, exhibit good supercapacitor performance. Many new electrode materials have been developed to play an essential role in capacitance behavior. This research focuses on the highly efficient application of nanostructured electrode materials such as nanoporous carbon and metal oxide CuO for supercapacitors. Nanopore carbon is made from coconut shell, which is synthesized using a simple heating method. Next, carbon nanopore and CuO nanoparticle composites were carried out with composition variations of 0.5,10,15, and 20% of the total weight. The results of cyclic voltammetry, electrochemical impedance spectroscopy, and charge-discharge tests, maximum results were obtained on a composition of 5% CuO nanoparticles with a capacitance of 280 F/gr and a conductivity of 1.14 X 10-2 S/cm. This result is due to an increase in the surface area between the pore surfaces, so more ions are trapped, causing the filling process to take place quickly.